Microwave engineering : fundamentals, design and applications - Kar, Subal (Universities Press, 2016)
Microwave engineering : fundamentals, design and applications / Kar, Subal. -- Kolkata: Universities Press, 2016 621.3813 K18 No. of Copies : 1